Determinants of Bank Lending Policy in the Context of Yemen - Al-Akari, Saleem; Slim, Chokri (Journal of Amran University, 2021)
The objective of this study is to identify the determinants of bank lending policy in the context of Yemen. To achieve this goal we try to study the probability of lending investment companies through a number of explanatory variables included in the multivariate model (Discriminate Analysis Model), and in the artificial intelligence model (Artificial Neural Network). To study our problem, we collected forty (40) actual cases of investment credit from eight Yemeni banks (28 agreement cases, 12 rejection cases). The two models have showed that the variable of guarantee has a significant influence on the decision-making process of bank lending policy. Decision makers in credit are based on a process of anticipation in the future. The findings indicated that most banks considered the type of guarantee as a key element to the success of lending decision, because, the guarantee is the best way for the bank to mulch the information asymmetries and to guard against the risk of non-repayment of loans.